Philosophical Modesty (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
In the article, I postulate a „philosophical modesty”. I elaborate on its understanding in the works of Jürgen Habermas and John Rawls. I reconstruct conditions („postmetaphysical thinking” and „reasonable pluralism”) in which philosophy operates today. I show what consequences they have for philosophy. I point to the substantial differences between these two thinkers.